From War to Peace in the Balkans, the Middle East and Ukraine - Serwer, Daniel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This open access book focuses on the origins, consequences and aftermath of the 1995 and 1999 Western military interventions that led to the end of the most recent Balkan wars. Though challenging problems remain in Bosnia, Macedonia, Kosovo, and Serbia, the conflict prevention and state-building efforts thereafter were partly successful as countries of the region are on separate tracks towards European Union membership. This study highlights lessons that can be applied to the Middle East and Ukraine, where similar conflicts are likewise challenging sovereignty and territorial integrity. It is an accessible treatment of what makes war and how to make peace ideal for all readers interested in how violent international conflicts can be managed, informed by the experience of a practitioner. Daniel Serwer is Professor and Director of the Conflict Management program at the Johns Hopkins School of Advanced International Studies, Johns Hopkins University, USA. .
1. Chapter 1: Introduction -- 2. Chapter 2: Why the Balkans? -- 3. Chapter 3: Bosnia: Prelude, Disease and Sequelae -- 4. Chapter 4: Macedonia: Timely Prevention Works -- 5. Chapter 5: Kosovo and Serbia: Loveless Marriage, Difficult Divorce -- 6. Chapter 6: The Balkans Region: Can It Join the West? -- 7. Chapter 7: What Should the Middle East and Ukraine Conclude From the Balkans?
Keywords: Peace; Europe$1 (BPolitics and government.s; Russia$1 (BHistory.s; Europe, Eastern$1 (BHistory.s; Soviet Union$1 (BHistory.s; Middle East$1 (BPolitics and government.s; Peace and Conflict Studies; European Politics; Russian, Soviet, and East European History; Middle Eastern Politics